2023
DOI: 10.1186/s12885-023-10572-4
|View full text |Cite
|
Sign up to set email alerts
|

Spectral CT-based radiomics signature for distinguishing malignant pulmonary nodules from benign

Abstract: Objectives To evaluate the discriminatory capability of spectral CT-based radiomics to distinguish benign from malignant solitary pulmonary solid nodules (SPSNs). Materials and methods A retrospective study was performed including 242 patients with SPSNs who underwent contrast-enhanced dual-layer Spectral Detector CT (SDCT) examination within one month before surgery in our hospital, which were randomly divided into training and testing datasets wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…The monoenergetic images with low keV can improve the contrast between iodine-containing pulmonary nodules and surrounding tissues, while CT SPN_40 keV , as the CT values measured by SPN on 40 keV monoenergetic images, can reflect the degree of enhancement of pulmonary nodules under 40 keV monoenergetic images, so it can indirectly reflect the blood supply in the lesions. Many previous studies have shown that the CT values of lesions on 40 keV monoenergetic images can distinguish benign and malignant lesions 16 , 27 , 28 . In a study by Zhang et al to differentiate between solitary lung adenocarcinoma and pulmonary tuberculosis, solitary lung adenocarcinoma had a higher CT 40 keV value in the arterial phase 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The monoenergetic images with low keV can improve the contrast between iodine-containing pulmonary nodules and surrounding tissues, while CT SPN_40 keV , as the CT values measured by SPN on 40 keV monoenergetic images, can reflect the degree of enhancement of pulmonary nodules under 40 keV monoenergetic images, so it can indirectly reflect the blood supply in the lesions. Many previous studies have shown that the CT values of lesions on 40 keV monoenergetic images can distinguish benign and malignant lesions 16 , 27 , 28 . In a study by Zhang et al to differentiate between solitary lung adenocarcinoma and pulmonary tuberculosis, solitary lung adenocarcinoma had a higher CT 40 keV value in the arterial phase 29 .…”
Section: Discussionmentioning
confidence: 99%